2014
DOI: 10.1016/j.cognition.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Rivals in the dark: How competition influences search in decisions under uncertainty

Abstract: In choices between uncertain options, information search can increase the chances of distinguishing good from bad options. However, many choices are made in the presence of other choosers who may seize the better option while one is still engaged in search. How long do (and should) people search before choosing between uncertain options in the presence of such competition? To address this question, we introduce a new experimental paradigm called the competitive sampling game. We use both simulation and empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 22 publications
3
48
0
Order By: Relevance
“…Second, several recent studies have shown that adolescents are more likely to engage in risky behavior when in the company of friends and peers than when alone65. A better understanding of how social context and peer pressure shapes individual approaches to ambiguity or uncertainty is therefore also important (e.g., competition has been shown to drastically curtail exploratory search66). Third, developmental differences in learning from feedback have been documented296768.…”
Section: Discussionmentioning
confidence: 99%
“…Second, several recent studies have shown that adolescents are more likely to engage in risky behavior when in the company of friends and peers than when alone65. A better understanding of how social context and peer pressure shapes individual approaches to ambiguity or uncertainty is therefore also important (e.g., competition has been shown to drastically curtail exploratory search66). Third, developmental differences in learning from feedback have been documented296768.…”
Section: Discussionmentioning
confidence: 99%
“…Exploration is less costly in non-competitive environments than in competitive environments; e.g., during mate choice in fish (Lindstrom & Lehtonen, 2013) and humans (Todd, 2007;Goldstone, Ashpole, & Roberts, 2005). The presence of competitors reduces information search in the "sampling paradigm" (Phillips et al, 2014). Exploration might be especially useful in competitive environments because it can help the agent to find a "niche" where he is better adapted than his competitors (Cohen et al, 2007;Schulze et al, in press).…”
Section: Factormentioning
confidence: 99%
“…Social factors of exploration/exploitation tradeoffs are often overlooked in the human decision making literature (for recent exceptions, see Goldstone, Ashpole, & Roberts, 2005;Phillips, Hertwig, Kareev, & Avrahami, 2014;Schulze, van Ravenzwaaij, & Newell, in press). In natural settings, however, agents rarely act in isolation from others, and exploration-exploitation tradeoffs can be different when considered at the group level than when considered for the individual agent.…”
Section: Social Factorsmentioning
confidence: 99%
“…Exploration may increase as norms become less valid as predictors of behavior-for example, when injunctive and descriptive norms (Cialdini et al, 1991) conflict; when conflicting injunctive norms imply opposite behaviors; or when a social domain is not (yet) governed by norms. Yet exploration may decrease further under competition (Phillips, Hertwig, Kareev, & Avrahami, 2014). In turn, nonsocial worlds can also offer environmental regularities (Pleskac & Hertwig, 2014) that may substitute for search.…”
Section: Discussionmentioning
confidence: 99%